Recovery education for people experiencing housing instability: An evaluation protocol. (September 2019) - Durbin, Anna; Kapustianyk, Grace; Nisenbaum, Rosane; Wang, Ri; Aratangy, Tatiana; Khan, Bushra; Stergiopoulos, Vicky
Background: Recovery education centers (RECs) offer recovery supports through education rather than traditional health services. The Supporting Transitions and Recovery Learning Centre (STAR) in Toronto, Canada, is among the few that are internationally focused on individuals with histories of homelessness. Although research suggests that RECs positively impact participants, there is a paucity of rigorous studies and none address the engagement and impacts on homeless individuals. Aims: This protocol describes a realist-informed evaluation of STAR, specifically examining (1) if STAR participation is more effective in promoting 12-month recovery outcomes than participation in usual services for individuals experiencing housing instability and mental health challenges and (2) how STAR participation promotes recovery and other positive outcomes. Methods: This study uses a quasi-experimental mixed methods design. Personal empowerment (primary outcome) and recovery, housing stability, social functioning, health service use and quality of life (secondary outcomes) data were collected at baseline, and 6 and 12 months. Intervention group participants were recruited at the time of STAR registration while control group participants were recruited from community agencies serving this population after screening for age and histories of housing instability. Interviews and focus groups with service users and providers will identify the key intervention ingredients that support the process of recovery. Results: From January 2017 to July 2018, 92 individuals were recruited to each of the intervention and control groups. The groups were mostly similar at baseline; the intervention group's total empowerment score was slightly higher than the control group's ( M ( SD ): 2.94 (0.23) vs 2.84 (0.28), p = .02), and so was the level of education. A subset of STAR participants ( n = 20) and nine service providers participated in the qualitative interviews and focus groups. Conclusion: This study will offer important new insights into the effectiveness of RECs, and expose how key REC ingredients support the process of recovery for people experiencing housing instability.